Strategi Pemerintahan Erdogan dalam Menghadapi Ancaman Politik dan Militer Suku Kurdi 2015-2019 - Nabiyyin, M. Hafizh (Jurnal ICMES, 2020)
In 2015, the conflict between the Turkish government and the Kurds - especially the members of Kurdistan Workers' Party (PKK) - again escalated. The escalation of the conflict between the two sides occurred due to the banning of PKK militants based in Turkey to help defend the City of Kobane in Syria - which is the Syrian Kurdish region - from the invasion of ISIS fighters. Consequently, cities in Turkey were targeted by sporadic attacks carried out by PKK militias. The spirit of independence and forming a self-governing territory from Turkey re-emerged. Derived on Barry Buzan's security perspective, this is a form of military and political threat to Turkey. Therefore, this paper intends to elaborate on the strategies adopted by the Turkish government in overcoming the threats of the Kurds using the theory of the International Society. The author concludes that the Turkish government adopted several policies to maintain territorial integrity and legitimacy of its sovereignty: (1) establishing cooperation with state and non-state actors; (2) conducting internal and external military operations; and (3) repressing pro-Kurdish journalists and politicians.